Do Open-end Funds Outperform Closed-end Funds? A Research on China's Mutual Funds Market. - ZHENG, YI (2006)
Mutual fund is one of the most popular investment tools in modern financial market. Mutual funds market of China was established from 1990s, so that the market mechanism and efficiency is not mature enough. It is necessary to consider the strategies and policies to improve mutual funds market in China. Nowadays, which kind of funds should be developed in the market is a controversial question. The problem that whether open-end funds outperform close-end funds in China's mutual funds market attracts more and more attention. Therefore, this dissertation proposes to focus on this problem and hopes to give some useful advice for the further study of mutual funds market in China.